Involvement of the maxillary sinus ostium (MSO) in the edematous processes after sinus floor augmentation: a cone-beam computed tomographic study - Shigeru Sakuma; Mauro Ferri; Hideki Imai; Natalia Fortich Mesa; Daniel José Blanco Victorio; Karol Alí Apaza Alccayhuaman; Daniele Botticelli (SpringerOpen, 2020)
Abstract Background After sinus floor augmentation, a thickening of the sinus mucosa has been described. The aim of the present study was to evaluate the involvement of the maxillary sinus ostium in the edematous processes after a sinus floor augmentation procedure. Methods Seventy-two cone-beam computerized tomographies (CBSTs) were taken before sinus floor augmentation and after 1 week and 9 months from surgery and analyses. Sinus mucosa thickness and area, ostium diameter and patency, and extension of the post-surgical transient mucosal thickening in relation to the ostium were evaluated on the CBCTs for all three periods. The term "virtual" when referring to sinus mucosa thickness and area was introduced because of the edema and bleeding that both contributed to a transient thickening and additional elevation of the sinus mucosa. Results The mean virtual thickness of the sinus mucosa was 2.7 ± 4.0 mm, 7.7 ± 7.1 mm, 1.7 ± 2.0 mm before surgery, and after 1 week and 9 months. The virtual mucosa area was 37.2 ± 52.5 mm2, 184.5 ± 153.8 mm2, and 34.0 ± 50.7 mm2. The ostium diameter at the three periods evaluated was 1.8 ± 0.5 mm, 1.1 ± 0.6 mm, 1.5 ± 0.8 mm, respectively. Three infundibula (4.2%) were found out of patency before surgery while this number increased to 14 (19.4%) after 1 week. Nine months after surgery, only one infundibulum (1.4%) was out of patency, however, without presenting signs of sinus pathologies. The extension of the mucosal edema on the palatal sinus was reduced after 9 months of healing. Conclusions One week after sinus floor augmentation, the maxillary sinus mucosa increased in dimensions and in several cases involved the ostium, reducing its diameter and producing a transient loss of patency. After 9 months of healing, the initial conditions were recovered.